Republic of Moldova : Financial System Stability Assessment. (IMF Staff Country Reports; Country Report, 2016)
Moldova has made some important advances since the 2008 FSAP Update. On the positive side, inflation has been brought down to single digits, the payment system has been upgraded, and important enhancements have been made to financial sector regulation and supervision. However, risks to banking sector stability have become severe. Large credit concentration and concealed connected lending, questionable cross-border exposures, and important data gaps mean that regulatory data likely significantly understate the system's vulnerability. Non-transparent ownership, weak governance, connected lending and weaknesses in regulatory powers and enforcement further exacerbate these risks and could limit the scope for an effective policy response to shocks. Governance structures, internal oversight processes, and risk management practices are poorly developed. In some cases, cross-border exposures are substantial and the pattern of some (particularly cross-border) financial transactions suggest a serious risk of money laundering.